How do vocational teachers learn? Formal and informal learning by vocational teachers in Kenya - Moses Njenga (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Context: Participation in Continuing Professional Development (CPD) supports the development of vocational teacher competencies. However, it is often not clear what learning methods vocational teachers use in their CPD. This study therefore investigated the CPD practices of vocational teachers in Kenya, with a specific focus on the formal and informal learning methods used. Approach: The study used a questionnaire survey to collect data from TVET teachers randomly drawn from six Technical and Vocational Colleges in Kenya's Nairobi Metropolitan Area. Descriptive and inferential analysis of the data was used to determine how frequently different learning methods are used and to identify associations between CPD practices and teacher characteristics. Findings: TVET teachers in Kenya were found to use different learning methods depending on the availability of the learning methods and the learning goals teachers have. Formal academic learning and discussions with colleagues are frequently used while collaborative learning methods and practice-based learning activities are less frequently used. Rarely used are written reflections about practice and its outcomes. Despite viewing Lecturer Industrial Attachment (LIA) as important and therefore wishing to attend LIA, more than a third of the participants indicated that they had never attended LIA. The use of professional literature is restricted to text books with limited use of primary and secondary literature. CPD activities such as mentoring, supervising other teachers, and school visits were found to form a unique category of CPD activities that is more frequently used by teachers with administrative responsibilities. Conclusion: The limited use of active learning methods that involve critical evaluation of practices and their outcomes risks limiting the ability of vocational teachers in Kenya to transform and adopt better practices. It is recommended that vocational teachers in Kenya are encouraged to adopt a broad conception of teacher CPD that embraces collaborative, reflective, and practice-based learning.
urn:nbn:de:gbv:18-10-1007-1
Keywords: 330; Teachers; Continuing Professional Development; Formal and Informal Learning; TVET (Technical Vocational Education and Training); Kenya; VET; Lehrkräfte; Lernmethode; Lernen; Kenia